Prevalence of post-traumatic stress disorder, emotional impairments, and fear in COVID-19 surviving patients - Luna-Rodríguez, Guadalupe Lizzbett; Peláez-Hernández, Viridiana; Orea-Tejeda, Arturo; Ledesma-Ruíz, Celia Deyanira; Casarín-López, Fernando; Rosas-Trujillo, Adrían; Domínguez-Trejo, Benjamín; Tepepa-Flores, Li Erandi (Frontiers in Virtual Reality, 2022)
Introduction: Among the different psychological sequelae in post-COVID syndrome, are symptoms related to emotional impairment, mostly depression, anxiety, and post-traumatic stress disorder (PTSD). Objective: To describe and to comparate the prevalence and severity of PTSD, anxiety, depression, and fear of COVID-19 in survivors three months after discharge from hospital. Method: A cross-sectional descriptive study was conducted, a total of 227 survivors COVID-19 patients participated; them were assessed three months following discharge hospital. A psychological evaluation focused on anxiety, depression, PSTD and fear was made. A statistical analysis through the t test for independent samples were performed. Results: The 64.5% of the patients were men, 60.9% required invasive mechanical ventilation (IMV) during hospitalization, the average age was about 48.23±14.33 years old. The 40% showed symptoms associated with PTSD, 38.4% exhibited anxiety, 36.6% depression, and 36.12% exhibited fear of COVID-19. There were statistically significant differences between men and women, in PTSD (t= -3.414, df=224, p=.001, x̅m= 5.10, x̅w=6.32), depression (t= -4.680, df=225, p=.000, x̅m= 3.64, x̅w=7.18), anxiety (t= -3.427, df=152.53, p=.001, x̅m= 3.78, x̅w=6.20) and fear of COVID-19 (t= -3.400, df=224, p=.001, x̅m= 11.88, x̅w=15.19). Furthermore, there were also statistically significant differences between the type of treatment during hospitalization (IMV vs without IMV), in PTSD (t=2.482, df=223, p=.014, x̅IMV= 5.21, x̅WIMV=6.08) and anxiety (t= -2.006, df=223, p=.046, x̅IMV= 4.05, x̅WIMV=5.44). Conclusion: Survivors of COVID-19 experience a high prevalence of PTSD, anxiety, depression, and fear, even three months after discharge from hospital. Females and patients who did not require IMV during hospitalization are the most affected population, presenting more severe symptoms of these psychological alterations. More research is required to know and observe the long-term evolution of these psychological alterations in this population.